2014
DOI: 10.1016/j.msec.2014.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Surface microcracks signal osteoblasts to regulate alignment and bone formation

Abstract: Microcracks are present in bone and can result from fatigue damage due to repeated, cyclically applied stresses. From a mechanical point, microcracks can dissipate strain energy at the advancing tip of a crack to improve overall bone toughness. Physiologically, microcracks are thought to trigger bone remodeling. Here, we examine the effect of microcracks specifically on osteoblasts, which are bone-forming cells, by comparing cell responses on microcracked versus non-microcracked hydroxyapatite (HA) specimens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Additionally, the presence of surface deformities such as crevices and micro‐cracks provided attachment points and topological cues for the cells. Micro‐cracks can enhance osteoblast attachment and alignment along their direction . On day 7, fluorescence microscopy showed MC3T3‐E1 cells attaching and aligning along a crack on the HAp surface (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, the presence of surface deformities such as crevices and micro‐cracks provided attachment points and topological cues for the cells. Micro‐cracks can enhance osteoblast attachment and alignment along their direction . On day 7, fluorescence microscopy showed MC3T3‐E1 cells attaching and aligning along a crack on the HAp surface (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Samples sintered at 1200°C for 5 hr exhibited surface deformities and micro‐crack formation, which have been reported to have both mechanical and biological benefits. Mechanically, micro‐cracks can help dissipate strain energy, thereby, increasing fracture toughness—a material property that is characteristically low for Hap . Additionally, Shu et al has reported that osteoblast attachment was significantly greater on HAp with induced micro‐cracks compared to HAp without the presence of micro‐cracks .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone matrix itself may play a role: a recent experiment by Shu et al bridges the gap between our work and that of Kennedy et al : they grew cells in vitro on the surface of a sample of hydroxyapatite (the mineral phase of bone). They found that introducing microcracks into the mineral enhanced osteoblast activity, possibly because those cells were sensing the calcium released during cracking . Further clues as to how this calcium release might stimulate altered cell behaviour come from recent in vitro work on notched bone samples …”
Section: Detection Of Microdamage In Bonementioning
confidence: 99%
“…They found that introducing microcracks into the mineral enhanced osteoblast activity, possibly because those cells were sensing the calcium released during cracking. 45 Further clues as to how this calcium release might stimulate altered cell behaviour come from recent in vitro work on notched bone samples. 46 It seems clear that the osteocyte network is acting as a mechanical transducer, sensitive to local changes caused by the presence of microcracks.…”
Section: E T E C T I O N O F M I C R O D a M A G E I N B O N Ementioning
confidence: 99%